Analyzing the Influence of Online Test-Driving Reviews on the Adoption of Autonomous Vehicles - Chuan Hui Liao; Xuan Zheng Wang; Ren Gang Guo; Siqi Wang (IEEE Access)
Autonomous vehicle (AV) technology has led to disruptive changes in transportation. Improving consumers’ trust and awareness of self-driving cars has become an urgent problem in market promotion and technological development. Besides the information provided by car makers and salespeople, consumers rely on information from online blogs and reviews, especially that provided by test drivers. This study explores the impact of test-driving reviews (TDRs) on the consumer decision-making process regarding the purchase and usage of AVs. We aim to understand whether and how different types of TDRs (professional, manufacturer, and amateur) affect consumers’ perceptions and attitudes toward AVs. Questionnaire surveys and structural equation modeling were used to test the hypotheses. The results indicate that both risk perception and perceived value significantly influence adoption intentions. For TDRs, positive professional reviews and manufacturer reviews reduced risk perception, leading to adoption intention. Both amateur reviews (AM) and manufacturer reviews (MR) positively influence perceived value, further increasing adoption intentions. Based on the analyses, manufacturers and policymakers were provided with practical implications for promoting AVs. Finally, this study has several limitations. First, it examines the influence of review channels on consumers’ purchase intentions of AVs, not actual purchasing behavior, warranting further exploration of this relationship. Additionally, the data were collected from China, so societal and cultural differences may affect the findings, highlighting the need to validate the model with buyers from other countries in future research.